Centuriación del territorio y modelación del paisaje en los llanos litorales de Barcino (Barcelona) y Tarraco (Tarragona): una investigación interdisciplinar a través de la integración de datos arqueomorfológicos y paleoambientales - Palet Martínez, Josep M.; Orengo, Hèctor A.; Riera-Mora, Santiago (Fabrizio Serra editore, 2010)
This paper deals with the contribution of Landscape Archaeology to the study of centuriations. The investigation is based on a diachronic and interdisciplinary perspective and explores the applicability of GIS. The article presents data from two case studies, the territories of Tarraco (Tarragona) and Barcino (Barcelona) offering some ideas about the meaning and function of Roman centuriations. Both territories show a strong territorial organization based on the model of centuriation, together with a complex land-use. Therefore, centuriations does not necessarily imply intensive landscape exploitation. In this sense, palaeoenvironmental evidence shows a Roman landscape characterized by the absence of both an extensive deforestation and a general extension of agricultural areas. The data reinforces the symbolic and representational meaning of the centuriation model.